Contemporary authors Volumes 93-96 - 4 0 16; Locher, Frances C.; 5 (Detroit, Michigan : Gale Research Company, 1980)
Contains alphabetically arranged profiles of contemporary authors in a range of media, including books, magazines, newspapers, television, radio, and film, each with personal data, addresses, career history, and a list of writings, and in some cases, a list of works in progress, sidelights, avocational interests, and an interview..
A bio-bibliographical guide to current writers in fiction, general nonfiction, poetry, journalism, drama, motion pictures, television, and other fields.
Includes bibliographical references.
Keywords: 2 -- 0; 6; Authors;Authors;Authors;Authors -- Biography.;Bio-bibliography.;Biography.;Bio-bibliography.; 20; 2